PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLANING UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS III SDN 192 PEKANBARU - kristiani panjaitan kristiani panjaitan; Lazim.N Lazim.N; Guslinda Guslinda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The background of this study is the low grade III social studies learning outcomes of SDN 192 Pekanbaru with KKM with an average of 71.11. with the aim of improving social studies learning outcomes in grade III by applying the cooperative learning model type student facilitator and explaning. This study uses the Classroom Action Research (CAR) design which consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were 27th grade A students consisting of 16 males and 11 females. The results showed that the classical completeness in the first cycle was 66.67% which had an increase in the second cycle of 85.19%. Teacher activities increased at each meeting, namely 75.00%, 83.33, 87.50% and 95.83%. Likewise, student activity experienced an increase in each of which was 70.83%, 79.16%, 91.66% and 95.83%. The average basic score to the first cycle increases by 1.56% and the base score to the second cycle increases by 21.35%. Based on the results of the research that has been carried out it can be concluded that the application of cooperative learning model type student facilitator and explaning can improve the learning outcomes of social studies class III SDN 192 Pekanbaru.